Interpellation and Stigmatization: Althusser and Goffman - Montag, Warren (Universidad de Costa Rica, 2020)
The essay explores some points of convergence between Louis Althusser and Erving Goffman, most visibly around the concepts of stigmatization and interpellation. Both explore the ways in which norms are imposed on already existing forms of individuality and corporeality, justifying sometimes violent procedures of control.